Air transport and the fate of pneumothorax in pleural adhesions. Issue 10 (October 1992) - Haid, M M; Paladini, P; Maccherini, M; Di Bisceglie, M; Biagi, G; Gotti, G
Abstract : Air travel is contraindicated in patients with a pneumothorax but was necessary because of the exigencies of war in three patients. Three patients with high velocity missile injuries to the chest and pleural adhesions are reported. All had to be evacuated by air, without an intercostal drain or oxygen supplement, from the war stricken area of Northern Somalia (Horn of Africa) to Mogadishu. Two patients with a partial pneumothorax flew on military transport aeroplanes at an altitude of 3000 m in a non-pressurised cabin and recovered rapidly after a few days in hospital. One patient, transported on a small Cessna aeroplane, died after developing bilateral tension pneumothoraces.